PERAN SEKRETARIS DALAM PROSEDUR ADMINISTRASI PENERBITAN IZIN TINGGAL TERBATAS DAN ETIKA PENERIMAAN TAMU DI KANTOR IMIGRASI KELAS I BANDUNG - Azizah, Nur (JURNAL ILMIAH EDUNOMIKA, 2024)
The Secretary has an important role in the service, either related to administrative tasks as well as service in the reception. Procedures of the Ministry of administration and the ethics of a good reception can avoid disappointment and dissatisfaction. A Secretary is required to be able to distinguish between providing services and able to exercise his duties, one of which, namely the administrative procedures in the exercise as well as the ethics of reception.The method of this research is a descriptive method. The technique of collecting data through observation of direct observations, interviews with the parties concerned, and the study of literature through his potretan camera, recording, copying and duplicating data. Based on the results of the research, the authors conclude that the role of the Secretary in the administrative procedures of the issuance of a residence permit is limited and the ethics of Immigration Office's reception class I Bandung has been running fine and according with the existing theory, but needs to be improved and good cooperation with the rest of the officers involved to complete its work effectively, efficiently and professionally. Keywords : The Role Of The Secretary In Administration, And Guest Service Ethics